Peran Burnout Syndrome sebagai Variabel Intervening dalam Hubungan antara Work–Life Balance dan Turnover Intention pada Dokter Umum RSUD Balaraja - Ilham Dianugraha; Arif Rachman; Rinawati Rinawati (Pusat riset dan Inovasi Nasional, 2026)
General practitioners play a crucial role in the delivery of healthcare services in public hospitals, where limited organizational resources and high service demands often place significant pressure on medical personnel. These conditions may disturb work–life balance, increase the risk of burnout syndrome, and ultimately lead to higher turnover intention. This study aimed to analyze the effect of work–life balance on turnover intention, with burnout syndrome acting as an intervening variable among general practitioners at RSUD Balaraja. An observational analytic design with a cross-sectional approach was applied, involving all 40 general practitioners working in the emergency department and inpatient units through a total sampling technique. Data were collected using standardized instruments, namely the Work–Life Balance Scale, Maslach Burnout Inventory, and the Intention to Quit Questionnaire. Data analysis was conducted using Spearman correlation and Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results revealed a significant relationship between work–life balance and burnout syndrome, as well as between work–life balance and turnover intention. Burnout syndrome was also significantly associated with turnover intention. Further analysis showed that work–life balance had both direct and indirect effects on turnover intention, with burnout syndrome partially mediating this relationship. In conclusion, work–life balance and burnout syndrome are important determinants of turnover intention among general practitioners. Therefore, hospital management should prioritize strategies such as workload regulation, enhanced organizational support, and burnout prevention to retain medical staff and maintain the quality of healthcare services in public hospitals.